Employee Performance in Primary Healthcare: The Roles of Competence, Motivation, and Workplace Empathy - Asniwati, Asniwati; Latief, Fitriani (Advances in Human Resource Management Research, 2026)
Purpose: This study examines the effects of competence, motivation, and workplace empathy on employee performance at the Takkalalla Community Health Center in Wajo Regency, while also identifying the most influential variable in the proposed model. Research Method: The study employed a quantitative case study design with census sampling, involving all 55 employees of the health center as respondents. Data were collected via a structured questionnaire using a 5-point Likert scale and analyzed in SPSS version 24. The analytical procedures included descriptive statistics, validity and reliability tests, classical assumption testing, multiple linear regression, partial t-tests, and coefficient-of-determination analysis. Results and Discussion: This study demonstrates that employee performance in the Takkalalla Community Health Center is significantly influenced by competence, motivation, and workplace empathy. The findings confirm that performance in primary healthcare is not determined solely by technical skills, but by the combined effects of cognitive, psychological, and interpersonal factors. Implications: These findings suggest that efforts to improve employee performance in primary healthcare should not focus solely on competence and motivation, but also on strengthening workplace empathy. The study contributes to policy and practice by proposing a more comprehensive performance model for community healthcare settings. Future research is recommended to test this model in broader healthcare institutions with larger samples and more diverse organizational contexts.